Greening the Workforce: A Strategic Way to Spur the Environmental Performance in the Hotel Industry - Nisar, Qasim Ali; Akbar, Ahsan; Naz, Shumaila; Haider, Syed Arslan; Poulova, Petra; Hai, Mahnoor Abdul (Frontiers in Environmental Science, 2022)
The study examines the role of green human resource management (GHRM) towards the environmental performance of hotels. It also investigates the crucial role of pro-environmental psychological capital, psychological green climate, and pro-environmental behaviors towards environmental performance. The target population consisted of green hotel employees. Data collected using a survey questionnaire from 374 employees was subjected to PLS-SEM for analysis. As per the findings, green human resource practices (green training & development, green performance management & appraisal, and green empowerment) are significant predictors for pro-environmental psychological capital, which further contributes positively towards the psychological green climate. It was also found that the psychological green climate is positively related to pro-environmental behaviors. Findings revealed that employees’ pro-environmental behaviors play a significant role to enhance the environmental performance of hotels. Moreover, it is indicated that Green HRM practices indirectly contribute to environmental performance through pro-environmental psychological capital, psychological green climate, and pro-environmental behaviors. This study is one of the few attempts to integrate the green HRM practices with pro-environmental psychological capital, green climate and pro-environmental behaviours to predict the environmental performance in hotels. It examines the moderating role of environmental consciousness that was almost ignored. This study is important for hotels that are trying to adopt green HR practices. It provided several suggestions to the practitioners while making the strategy to promote environmental performance with the help of green HR practices through various ways. It also assist the hotel management to enhance pro-environmental psychological capital by promoting green recruitment & selection, green training & development, green performance management & appraisal, and green empowerment for the promotion of environmental performance.